2015
DOI: 10.1080/00958972.2015.1072624
|View full text |Cite
|
Sign up to set email alerts
|

Enabling visible-light water photooxidation by coordinative incorporation of Co(II/III) cocatalytic sites into organic-inorganic hybrids: quantum chemical modeling and photoelectrochemical performance

Abstract: Coordinative incorporation of Co(II/III) cocatalytic sites into organic-inorganic hybrids of TiO 2 and "polyheptazine" (PH, poly(aminoimino)heptazine, melon, or "graphitic carbon nitride") has been investigated both by quantum chemical calculations and experimental techniques. Specifically, density-functional theory (DFT) calculations (PBE/def2-TZVPP) suggest that Co(II/III) and Zn(II) ions adsorb in nanocavities at the surface of the hybrid PH-TiO 2 cluster, a prediction which can be further confirmed experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…[53] The optical absorption edge of the hybrid photoanodes (~ 2.6 eV, ~ 477 nm) determined from the Tauc plots (Supporting Information, Fig. S4) is larger than the value typically obtained in our previous studies (~ 2.3-2.5 eV), [24,[32][33][34][35][36][37][38] which can be explained by the inherent limitations of the Tauc formalism as applied for bandgap determination of hybrid materials, [54] and to the fact that in previous studies we determined the bandgap using the Kubelka-Munk function calculated from diffuse reflectance spectra of corresponding powders, while here we use absorptance data obtained from measurements on complete photoanodes. Notably, the change in electronic absorption properties upon the deposition of the CoPOM catalyst is negligible, which indicates that the parasitic light absorption by the CoPOM catalyst is very low.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…[53] The optical absorption edge of the hybrid photoanodes (~ 2.6 eV, ~ 477 nm) determined from the Tauc plots (Supporting Information, Fig. S4) is larger than the value typically obtained in our previous studies (~ 2.3-2.5 eV), [24,[32][33][34][35][36][37][38] which can be explained by the inherent limitations of the Tauc formalism as applied for bandgap determination of hybrid materials, [54] and to the fact that in previous studies we determined the bandgap using the Kubelka-Munk function calculated from diffuse reflectance spectra of corresponding powders, while here we use absorptance data obtained from measurements on complete photoanodes. Notably, the change in electronic absorption properties upon the deposition of the CoPOM catalyst is negligible, which indicates that the parasitic light absorption by the CoPOM catalyst is very low.…”
Section: Resultscontrasting
confidence: 54%
“…[36] This result is also in line with our previous studies that confirmed that the presence of an effective OER catalyst is absolutely necessary to observe oxygen as a product of water oxidation at CNx-TiO2 hybrid photoanodes. [24,[32][33][34][35][36][37][38][39] On the other hand, CNx-free pristine TiO2 photoanodes modified with CoPOM exhibited neither photocurrents nor oxygen evolution since pristine TiO2 does not absorb in the visible range. The apparent (based on dissolved O2 and uncorrected for losses in the headspace) Faradaic efficiencies (FE) of oxygen evolution for CoPOM-PEI-CNx-TiO2 (15% ± 4%) and for CoPOM-CNx-TiO2 (12% ± 4%) are rather low, which suggest that even in the best photoanodes the overall utilization of holes generated in CNx for water oxidation is still far from optimum, and a substantial portion of holes does not induce the OER but instead contributes to the photocorrosion of CNx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, we have investigated hybrid photoanodes based on nanocrystalline TiO 2 electron collector modified with polymeric carbon nitride ("CN x ," also called polyheptazine or, more precisely, poly(aminoimino)heptazine or melon, a polymeric s-heptazine derivative, also referred to as "graphitic carbon nitride" or "g-C 3 N 4 " in the literature) (Wang et al, 2010), coupled with IrO x , CoO(OH) x or NiO x cocatalysts (Bledowski et al, 2012(Bledowski et al, , 2013(Bledowski et al, , 2014, Wang et al, 2017Mei et al, 2013;Khavryuchenko et al, 2015;Longchin et al, 2020). Such hybrid electrodes can be readily prepared by depositing CN x into a mesoporous TiO 2 anatase film on fluorine-doped tin oxide (FTO) glass by chemical vapor deposition from urea pyrolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…43 Herein, the OER and HER catalysts, which can be inorganic metal-based nanoparticles (NPs) electrode sensitized by a trisbipyridine ruthenium complex coupled to an iridium oxide catalyst, about fifteen examples have been reported. In addition to trisbipyridine ruthenium complexes, [46][47][48][49][50][51][52][53] organic photosensitizers of the type polyheptazine, [54][55][56][57][58][59][60] perylene, [61][62][63] π-conjugated naphthalene benzimidazole polymer 64 and freebase porphyrin, 51 have been employed in association with IrO x or CoO x OER catalysts. Basically, these hybrid photoanodes comprise a transparent doped semi-conducting electrode (Indium Thin Oxide (ITO) or Fluoride Thin oxide (FTO)) covered with a n-type SC such as TiO 2 , SnO 2 or WO 3 on which the molecular PS is adsorbed, generally in mono-layer, as well as the MO x (nano)particles deposited by a chemical or photoelectrochemical way.…”
Section: Introductionmentioning
confidence: 99%